Culture and waste: a socio-cultural study of household solid waste management practices - Fakunle, Sunday Olutayo; Ajani, Albert Oludele (Frontiers in Sustainability, 2026)
IntroductionStudies have reported inadequate levels of individual participation in sustainable household solid waste (HSW) management practices, a limited number of indigenous studies have considered cultural factors as a possible underlying influence on handling the waste. Therefore, this study explored the influence of cultural elements on the practices used to manage HSW.MethodsThe study was carried out in four purposively selected quarters, namely Moore, Iremo, Ilode, and Ilare in Ile-Ife, southwestern Nigeria. Within each quarter, convenience sampling was employed to select 9 participants for face-to-face in-depth interviews, resulting in a total sample size of 36 participants. Content and thematic analysis methods were utilised to analyse the data collected.ResultsThe study identified various cultural elements, such as cultural norms, symbols, values, beliefs, conventions, and religious practices, as influential factors shaping household solid waste management practices, including zero waste, waste reduction or minimisation, waste-to-wealth, waste-to-energy, reuse, waste exchange, waste gifting, landfilling, dumpsite usage, incineration, and others. The study concluded that Yoruba cultural elements such as values, beliefs, norms, and customs concurrently negatively and positively influence several practices to manage HSW. These practices ranged from the exchange of waste for a new household item, a system that resembled the conventional trade-by-barter system, waste gifting, waste to cash, and waste to energy. Other practices included burning, landfilling, and using (informally) designated dumps.DiscussionThe study confirmed the role of culture in the adoption of these disposal practices among Yoruba residents of the study location. This confirmation manifested in the practice of reciprocity, gathering materials to build spirits’ abodes, the belief that nature will take care of the waste as one of its components, the belief that burning enhances soil fertility, the custom of using the ashes from the burning, and the belief in the role of social norms and economic status.